Character Building of Students During the Covid-19 Pandemic with Digital Literacy Media Civics Caring Apps - Ammatulloh, Mutiara Imtisyal (Universitas Pendidikan Indonesia (UPI), 2021)
This research presents an approach in cultivating and shaping the character of students at the elementary school level through Prototype Civics Caring (Character Building) Apps as an Android-based learning media that integrates learning models Value Clarification Technique (VCT) with games-based learning methods. Currently there are many applications that aim to instill character education in children, but not many applications provide an introduction to character building from the perspective of children and parents, testing understanding, and monitoring student activities, as well as testimonials that parents or guardians can fill out in every month. During the Covid-19 pandemic, learning activities were carried out online, which of course decreased the effectiveness of teachers in controlling the character building of students. Therefore, the Civics Caring Apps Prototype presents a character values planting scheme that aims as a special medium that can monitor and control the character formation of students.The method used is the design and development (DD) model research method or design and development. The data collection method is done by studying literature, interview, and questionnaire. The contribution of research to science includes the field of Citizenship Education and the field of Sociology. The results of this study are user tasks, evidence of student character changes, prototype design and android applications in providing understanding of character values with good user experience and interactive content display to motivate students to implement each positive character value they learn.